Novel techniques for modeling of laser-plasma interactions in particle-in-cell codes for use in hohlraum simulations - Thoma, Carsten H.; Welch, Dale R.; Clark, Robert E.; Rose, David V (2016 IEEE International Conference on Plasma Science (ICOPS), 2016)
In the NIF hohlraum gold walls are heated by laser beams (I ∼ 1015 W/cm2, λ = 1/3 μm pulse lengths ∼ 1 ns), with collisional absorption believed to be the primary heating mechanism. X-rays generated by the hot ablated plasma at the gold walls are then used to implode a target in the hohlraum interior. In addition to the collisional absorption of laser energy at the walls, non-linear laser plasma interactions, such as two Plasmon decay, are believed to generate a population of supra-thermal electrons which, if present, can have a deleterious effect on target implosion. With an eye toward performing large-scale hohlraum simulations we have introduced a new capability into a hybrid particle-in-cell code which allows modeling of collisional absorption by using by a ray-tracing technique which does not require the resolution of the laser wavelength. This allows us to do relatively large scale (i.e. hohlraum-sized) simulations with a reasonable number of cells. But the non-linear effects which are believed to be the cause of hot electron generation can only be fully captured by fully kinetic simulations with good resolution of the laser wavelength. For this reason we employ a two-tiered approach to hohlraum modeling. An initially thin blowoff plasma is assumed to be present at the walls. Large-scale simulations (Δx > λ) of the collisional absorption process can be conducted using fast quasi-neutral algorithms with fluid species. From these simulations, we can observe the time evolution of the hohlraum walls and characterize the density gradients. From these results we can transition to smaller-scale highly-resolved (Δx << λ) simulations using traditional kinetic PIC methods, from which we can fully model all of the non-linear laser-plasma interactions, and assess the details of the electron distribution function.